Pengembangan Alat Pendeteksi Kebakaran Berbasis Sensor untuk Keamanan Elektronik: Pengembangan Aplikasi Mobile dan Alat Pendeteksi Kebakaran Berbasis Sensor untuk Keamanan Elektronik - Shofiyullah, R. Muhammad Azmi Herdi; Bagus Prasetyo, Iqshan; As’as Prabowo, Muhammad; Andhani, Ramona; Nugroho Pramudhita, Agung (Komputika : Jurnal Sistem Komputer, 2024)
The use of electronic devices has become common in today's era, both in industries and in everyday life. However, the potential fire hazards posed by these devices, such as gas stoves and industrial equipment, need to be taken seriously. Despite the installation and maintenance measures taken to reduce risks, there are still other factors that can trigger fires. Therefore, it is important to develop a fire detection tool that can provide information about the room conditions so that appropriate preventive measures can be taken before or during a fire incident. By utilizing temperature and humidity sensors like DHT22, as well as smoke sensors like MQ2, a fire detection device can be designed. Through the use of these sensors and suitable programming, the system is capable of providing real-time room condition information and sending notifications when significant changes occur. The experimental results have shown that the system is responsive to changes in room conditions and capable of providing early warnings regarding potential fires.